Yam urban market characteristics and consumer preferences in Bukavu City, eastern D.R. Congo - Mondo, J.; Mugisho, G.M.; Chuma, G.B.; Agre, A.P.; Banda, V.R.; Adebola, P.O.; Asfaw, A. (Frontiers Media, 2025)
Demand-led breeding is essential for developing crop varieties that suit market requirements. This study employed surveys targeting both yam (Dioscorea spp.) traders and consumers in Bukavu city, eastern Democratic Republic of Congo (DRC), to assess yam market characteristics and trait preferences. The results showed that the yam market operates predominantly informally and is dominated by women traders. The peak supply period occurs from March to May, characterized by relatively stable prices, while yam availability gradually decline and rare from August to January, prompting price increases of approximately 23% towards October. Income from yam trade plays crucial role in meeting family basic needs, including food, child education, and healthcare expenses, underscoring its importance for food and income security in the community. Market surveys, household interviews, and regression analyses consistently identified taste, softness, tuber flesh color, tuber shape, and tuber size as primary varietal preference criteria in urban settings, with slight differences across gender and age groups. Socioeconomic factors such as household location, education level, dietary integration of yam, and awareness of its nutritional benefits emerged as key drivers of urban yam consumption, regardless of gender and age categories. Our study helped to differentiate four market segments and develop corresponding target product profiles (TPPs) to inform yam breeding initiatives tailored to the needs of eastern DRC. These findings provide valuable insights into yam market characteristics, its role in sustaining livelihoods, and priority traits that should be addressed by plant breeding to enhance urban consumption.